Primary hypothyroidism in childhood cancer survivors: Prevalence, risk factors, and long‐term consequences. Issue 3 (13th October 2021) - Chemaitilly, Wassim; Li, Zhenghong; Brinkman, Tara M.; Delaney, Angela; Huang, Sujuan; Bjornard, Kari L.; Lam, Catherine G.; Wilson, Carmen L.; Barnes, Nicole; Clark, Karen L.; Krasin, Matthew J.; Metzger, Monika L.; et al.
Abstract : Background: Data on primary hypothyroidism and its long‐term impact on the health, cognition, and quality of life (QOL) of childhood cancer survivors are limited. This study examined the prevalence of and risk factors for primary hypothyroidism and its associations with physical, neurocognitive, and psychosocial outcomes. Methods: This was a retrospective study with a cross‐sectional health outcome analysis of an established cohort comprising 2965 survivors of childhood cancer (52.8% male; median current age, 30.9 years, median time since cancer diagnosis, 22.3 years). Multivariable logistic regression estimated odds ratios (ORs) and 95% confidence intervals (CIs) for associations between primary hypothyroidism and cancer‐related risk factors, cardiovascular disease risk factors, frailty, neurocognitive and QOL outcomes, social attainment, and subsequent thyroid carcinoma. Associations between serum free thyroxine and thyrotropin levels at assessment and health outcomes were explored. Results: The prevalence of primary hypothyroidism was 14.7% (95% CI, 13.5%‐16.0%). It was more likely in females (OR, 1.06; 95% CI, 1.03‐1.08), was less likely in non‐Whites (OR, 0.96; 95% CI, 0.93‐0.99), was associated with thyroid radiotherapy (higher risk at higher doses), and was more common if cancer was diagnosed at an age ≥ 15.0 years versus an age < 5 years (OR, 1.05; 95% CI, 1.01‐1.09). Primary hypothyroidism was associated with frailty (OR, 1.54; 95% CI, 1.05‐2.26), dyslipidemia (OR, 1.52; 95% CI, 1.14‐2.04), impaired physical QOL (OR, 1.66; 95% CI, 1.12‐2.48), and having health care insurance (OR, 1.51; 95% CI, 1.07‐2.12). Conclusions: Primary hypothyroidism is common in survivors and is associated with unfavorable physical health and QOL outcomes. The impact of thyroid hormone replacement practices on these outcomes should be investigated further. Abstract : In this study, primary hypothyroidism affects 14.7% of 2965 survivors of childhood cancer, and it is associated with adverse health and quality of life. Associations between thyroid function tests and health outcomes are explored.